Pengaruh Penerapan Sistem E-Filing, Program Pengungkapan Sukarela Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Di KPP Pratama Suarabaya Karangpilang - Devi Rahma Wati; Surenggono (INTELLECTUAL CAPITAL, Jurnal Akuntansi Kontemporer, 2024)
The purpose of this research is to find out "whether the implementation of the e-filing system, voluntary disclosure programs and tax sanctions have an impact on individual taxpayer compliance at KPP Pratama Surabaya Karangpilang". The approach used is quantitative research which is focused on examining the relationship between variables. The population of this study is WPOP registered at KPP Pratama Surabaya Karangpilang. Purposive sampling was used with WPOP criteria having an NPWP and registered at KPP Pratama Surabaya Karangpilang. 110 respondents were samples that were processed by distributing questionnaires offline by coming to KPP Pratama Surabaya Karangpilang as data collection. IBM Statistics SPSS version 25, multiple linear regression was performed to analyze the data. Based on research findings, the implementation of the e-filing system, the Voluntary Disclosure Program, and Tax Sanctions have a significant effect on individual taxpayer compliance at KPP Pratama Surabaya Karangpilang.